2019
DOI: 10.2495/tdi-v3-n2-117-131
|View full text |Cite
|
Sign up to set email alerts
|

Train rescheduling plan generation based on train route combination considering rolling stock types

Abstract: Railway transport has high punctuality, however, sometimes accidents happens due to facility failure or natural disasters, and the operation needs to change from its original scheduled timetable. When the operation has to return to the original schedule that operation is called "train rescheduling". Automatic rescheduling methods have been suggested considering several operation conditions and operation environments. During the rescheduling, the operated rolling stock types must be considered because different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Jiang et al (2019) identified the main variables that contribute to train delay and constructed different model to predict the primary delay recovery [21]. Katori and Izumi (2019) described how to generate automatic rescheduling methods while specifically considering the operated rolling stock types [22]. Josyula et al (2018) presented the solution space of the train rescheduling problem as a binary tree and designed and implement two fast heuristic algorithms-a sequential, and a parallel [23].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al (2019) identified the main variables that contribute to train delay and constructed different model to predict the primary delay recovery [21]. Katori and Izumi (2019) described how to generate automatic rescheduling methods while specifically considering the operated rolling stock types [22]. Josyula et al (2018) presented the solution space of the train rescheduling problem as a binary tree and designed and implement two fast heuristic algorithms-a sequential, and a parallel [23].…”
Section: Related Workmentioning
confidence: 99%
“…(2019) identified the main variables that contribute to train delay and constructed different model to predict the primary delay recovery [21]. Katori and Izumi (2019) described how to generate automatic rescheduling methods while specifically considering the operated rolling stock types [22]. Josyula et al.…”
Section: Related Workmentioning
confidence: 99%